More 'milk' than 'psychology or tablets': Mental health professionals' perspectives on the value of peer support workers - Timothy Moore; Laetitia Zeeman (Wiley, 2021)
Abstract Background Though growing numbers of peer support workers are employed in the UK National Health Service (NHS), conflicts persist between core values of peer support and values which exert power within these services. Objectives To explore what NHS mental health professionals value about the peer support worker role. Design Five professionals from different professions and mental health settings were interviewed twice. The first interviews explored their experiences of working with peers. Transcripts were analysed using discourse analysis and psychosocial theory. Second interviews allowed participants to respond to the analysis and influence subsequent analysis. Results Mental health professionals valued peers for the deeply empathic, relational approach they brought, based in their subjective experience. Peer work was also valued for the affect‐focused quality of this work, and the challenge peers pose to existing values in mental health services. The values of peer support troubled dominant ways of working based in forms of knowledge that favour objectivity and hence encountered challenges. Conclusions Peers fulfil the role of amplifying the status of diverse forms of knowledge, values and related ways of working that have become marginalized in NHS mental health services. It is important that peers are not seen as an isolated solution to the marginalization of these forms of knowledge and values, but that their way of working becomes reflected in other roles whilst evoking change throughout these services. Patient or Public Contribution Patient and Public Involvement groups were consulted both in the design and analysis stages of the study.